Neurogenesis and progenitor cell distribution in the subgranular zone and subventricular zone of the adult sheep brain - Low, V.F.; Faull, R.L.M.; Bennet, L.; Gunn, A.J.; Curtis, M.A. (Neuroscience, 2013)
•We studied adult sheep neurogenic niches after administering BrdU.•Progenitor cell distribution in the sheep subventricular zone is similar to humans.•The sheep subventricular zone has far more progenitors than the hippocampus.•The overall structure of the sheep subventricular zone is similar to humans. Progenitor cell proliferation is ubiquitous in the subventricular zone (SVZ) and subgranular zone (SGZ) of adult mammalian brains, however, the abundance and distribution of proliferation are surprisingly heterogeneous between species. In rodents, proliferation is high in both the SVZ and SGZ, while in humans proliferation is prominent in the SVZ but limited in the SGZ. To accurately study proliferation and how it changes in human disease, we should focus on animals in which the patterns of proliferation are consistent with the human brain. In this study, we characterized the neurogenic niches of the adult sheep, an animal model with a longer lifespan than rodents and a highly gyrencephalic brain, using 5-bromo-2′-deoxyuridine (BrdU) as a mitotic marker and neuronal nuclear antigen to identify neuronal lineage cells. Our study demonstrates that the sheep SVZ is organized into the same distinct layers that are comparable to what has been described in humans. The rate of maturation of new neurons was slower in sheep than in previous reports in rodents, with only 20% of BrdU-positive cells showing neuronal phenotype after 4 months survival following BrdU administration. Most importantly, as in the human, there was much greater proliferation in the sheep SVZ than in the SGZ. These results suggest that the sheep is a better basis for comparisons with human SVZ and SGZ neurogenesis than rodents.